Year level, age, sex, mode of entry, and frequency of library use as correlates to the academic performance of BLIS students at U.P. Diliman - Lobo, Marie Joie A.; Buenrostro, Juan Jr. C. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 1998)
This study aims to determine the correlation of year level, age, sex, mode of entry and frequency of library use to the academic performance of BLIS students at U.P.
The descriptive method of research was used in this study. Questionnaire was the instrument used in gathering data. One hundred questionnaires were distributed but only 76 returned. Chi-square tests, percentages and cross tabulations were used in analyzing the data that were collected.
Results showed that there was no significant correlation between the age and academic performance of the students. Based on these results, the following conclusions were drawn: The academic performance of the first and third years were higher than that of the second and fourth years; there were more females who got higher academic performance than males; the transferees from other schools tend to have higher academic performance while the shiftees tend to have lower academic performance; and the more frequent users of the library have higher academic performance than the less frequent users.
Computer print out.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: University of the Philippines, Diliman. Institute of Library Science -- Students